Nectar gaze and poison breath: an analysis and translation of the Rajasthani oral narrative of Devnārāyaṇ - Malik, Aditya (Oxford University Press, 2005)
Offers a study of "Devnarayan ki par", along with an English translation of this Rajasthani oral narrative. Using the narrative, this book explores a range of questions relevant to the study of Indian folk culture and Hinduism as a whole: how is orality conceptualized and practiced? What is the relationship between spoken and visual signs?
Keywords: Volksliteratur; Mārwārī; Rājasthānī; Devnārāyaṇ